Girls on the edge : the four factors driving the new crisis for girls : sexual identity, the cyberbubble, obsessions, environmental toxins - Sax, Leonard (New York : Basic Books, 2010)
Girls are cutting themselves with razors. Girls are convinced they're fat, and starve themselves to prove it. Other girls are so anxious about grades they can't sleep at night--at eleven years of age. What's going on? Here, family psychologist Dr. Leonard Sax provides the answers. He shares stories of girls who look confident and strong on the outside, but are fragile within. He shows why a growing proportion of teen and tween girls are confused about their sexual identity, or are obsessed with grades or Facebook. Dr. Sax provides parents with tools to help girls become confident women, along with practical tips on helping your daughter choose a sport, nurturing her spirit through female-centered activities, and more.--From publisher description.
Introduction: three girls -- First factor: sexual identity -- Second factor: the cyberbubble -- Third factor: obsessions -- Fourth factor: environmental toxins -- Mind -- Body -- Spirit.
Includes bibliographical references (pages 219-245) and index.
Keywords: Body image in adolescence; Sex in popular culture; Girls -- Psychology; Girls -- Health and hygiene; Gender identity